Effectiveness of transabdominal ultrasonography in predicting clinical relapse of Crohn’s disease - Shinya Fukushima; Takehiko Katsurada; Mutsumi Nishida; Satomi Omotehara; Kensuke Sakurai; Kana Yamanashi; Reizo Onishi; Naoya Sakamoto (Intestinal Research, 2024)
Background/Aims Transabdominal ultrasonography (US) helps evaluate Crohn’s disease (CD) activity. We investigated whether the US could predict subsequent adverse outcomes for patients with CD in clinical remission. Methods This single-center retrospective study included patients with CD in clinical remission who underwent US between April 2011 and April 2021, focusing on the predictability of subsequent adverse outcomes within 5 years. We used the US-CD, which was calculated using multiple US findings. Predictive variables were assessed using Cox proportional hazards regression analysis, and the predictive value was evaluated using receiver operating characteristic curves. Results Seventy-three patients were included. During a median follow-up of 1,441 days (range, 41–1,825 days), 16.4% (12/73) experienced clinical relapse, 9.6% (7/73) required endoscopic balloon dilation (EBD), 58.9% (43/73) required enhanced treatment, and 20.5% (15/73) underwent surgery. In the multivariate analysis, US-CD was significantly associated with clinical relapse (P= 0.038) and the need for enhanced treatment (P= 0.005). The area under the receiver operating characteristic curve for predicting clinical relapse and the need for EBD was 0.77 and 0.81, respectively, with US-CD (cutoff value = 11), and that for requiring enhanced treatment was 0.74 with US-CD (cutoff value = 6). Patients with US-CD ≥ 11 demonstrated a significantly higher occurrence of clinical relapse (P= 0.001) and EBD (P= 0.002) within 5 years. Patients with US-CD ≥ 6 experienced a significantly higher likelihood of requiring enhanced treatment (P< 0.001) within 5 years. Conclusions High US-CD is associated with subsequent adverse outcomes in patients with CD.